Distance professional qualification to promote adequate and healthy eating: factors associated with dropout - Mariana Souza Lopes; Izabela Santana Sathler; Cheila de Sousa Jardim Soares; Nathália Luíza Ferreira; Aline Cristine Souza Lopes (Epidemiologia e Serviços de Saúde, 2025)
Abstract Objective To analyze factors associated with dropout from a distance professional qualification course on promoting adequate and healthy eating in Brazil. Methods This is a cross-sectional study with professionals from the Brazilian National Health System (Sistema Único de Saúde - SUS) enrolled in a distance learning course, provided between 2019 and 2020, based on Ministry of Health educational materials. Sociodemographic and professional data associated with dropout from the course were assessed, using multiple logistic regression (p-value<0.05). Results Dropout prevalence was 30.6%. It was was associated with living in the Northern macroregion (p-value 0.009) and the Northeast macroregion (p-value<0.001), being a nurse (p-value<0.001), having lower levels of higher education (degree: p-value 0.004; specialization/residency: p-value 0.025), having worked in the SUS for longer (p-value 0.004), having taken the course using a cell phone or tablet (p-value 0.024), having previous training on adequate and healthy eating (p-value 0.007) and not having previously used the course materials (p-value 0.021). Conclusion Dropout was greater among nurses, professionals from the North and Northeast macroregions, those with a lower level of higher education, longer experience in the SUS, and among those who accessed the course mainly via cell phone or tablet, those who had previously participated in professional training on the theme and those who had not previously used the materials presented during the course. Changing these factors requires institutional support, with integration of the country’s federative units, aiming to overcome local challenges faced by professionals in completing continuing education activities.